Pengaruh Harga dan Diskon terhadap Keputusan Pembelian Produk Shopee pada Generasi Z Kota Depok - Irma Suryani; Rani Kurniasari (PPIMAN Pusat Publikasi Ilmu Manajemen, 2024)
The effect of prices and discounts on purchasing decisions for shopee products on Generation Z in Depok City, the method used in this research is quantitative and the data collection technique is documentation study, besides that the data processing uses the SPSS version 25 application. The instrument used to collect data is a questionnaire. This research was conducted in April-June 2024. Respondents in this study were Generation Z Depok City who purchased facial care products at Shopee, totaling 400 people. And distributing questionnaires with each variable, namely variable X1 price, X2 discount, and Y purchase decision. Quantitative analysis consists of data quality testing (Validity and Reliability), classical assumption test, multiple linear analysis, hypothesis testing (T Test and F Test), and determination coefficient test. The results of this study are in line with research conducted by Devi Marta Dwi L., Theresia Pradiani, and Ike Kusdyah Rachmawati, in 2021. It can be said that the price and discount variables together have a significant effect on the variable purchasing decisions for facial care products at Shopee for Generation Z in Depok City.